1996
DOI: 10.1073/pnas.93.15.8046
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic agonists stimulate secretion of soluble full-length amyloid precursor protein in neuroendocrine cells.

Abstract: The Af3 peptide of Alzheimer disease is derived from the proteolytic processing of the amyloid precursor proteins (APP), which are considered type I transmembrane glycoproteins. Recently, however, soluble forms of full-length APP were also detected in several systems including chromaffin granules. In this report we used antisera specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 46 publications
5
52
0
1
Order By: Relevance
“…The release of full-length APP was also demonstrated to be stimulated by cholinergic agonists (52). These data, together with the data from this study, show that APP and its catabolites can be released associated with exosomes and that this process is likely modulated by several parameters.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The release of full-length APP was also demonstrated to be stimulated by cholinergic agonists (52). These data, together with the data from this study, show that APP and its catabolites can be released associated with exosomes and that this process is likely modulated by several parameters.…”
Section: Discussionsupporting
confidence: 48%
“…These APP fragments are also co-sedimented with markers of exosomes at a sucrose density corresponding to that described for exosomes (50,51). The presence of soluble full-length APP in the medium was demonstrated previously in cells transfected with APP, but remained unexplained (52,53). Secretion of APP within exosomes is con- sistent with these observations and could be an explanation.…”
Section: Discussionmentioning
confidence: 95%
“…Although it is clear that M1 and M3 receptors (muscarinic acetylcholine receptors) activate protein kinase C (PKC), augment production of nonamyloidogenic fragments of APP, and inhibit A␤ production, some studies have shown that nAChRs can also influence APP metabolism and toxicity (for review see Roberson and Harrell, 1997;Auld et al, 1998). Activation of nAChRs has been shown to increase the secretion of nonamyloidogenic fragments of APP from PC12 cells, an effect that requires extracellular Ca 2ϩ (Efthimiopoulos et al, 1996;Kim et al, 1997). It is therefore possible that cholinergic transmission influences APP metabolism via both muscarinic and nicotinic receptors.…”
Section: Neuronal Nachrs and Neuroprotectionmentioning
confidence: 99%
“…A single chain antibody fragment engineered from a catalytic V L domain degraded APP (31), highlighting the risk of interference in APP function. Intact, fulllength APP is found physiologically in two forms: the membrane-bound form and the soluble, secreted form (32,33). nIgV 2E6 did not digest the purified soluble APP substrate detectably (Fig.…”
Section: Igv 2e6 Hydrolytic Properties-recombinantmentioning
confidence: 99%